The Role of Values in Maintaining Ecological Balance in New Uzbekistan - Xudaynazarov Samad Xudayberdievich (Web of Scientist International Scientific Research Journal, 2025)
This article explores the role of values in maintaining ecological balance in New Uzbekistan. In the article, environmental values are understood as beliefs, principles and practices aimed at respect for nature, rational use of resources and Environmental Protection. The article will analyze the environmental policies and strategies of the New Uzbekistan, including measures for the transition to a "green economy", the expansion of the use of renewable energy sources and the development of environmental education. The role of family, school, media and non-governmental organizations is emphasized in the formation of environmental values. In conclusion, maintaining ecological balance is one of the priorities of the New Uzbekistan, and the role of values in this regard is incomparable. By promoting and developing environmental values, Uzbekistan can achieve sustainable development and provide a healthy environment for future generations